Guidelines on designing conceptual framework for strategic management with application to the energy industry - Maryam Ayoubi; Ehsan Mehrabanfar; Audrius Banaitis (Administrative Sciences, 2018)
The role of strategic management is to handle the day-to-day needs of the firms with respect to current events of fluctuating markets so that they can effectively reach to their pre-planned, long-term goals. This study aims to explain the steps taken to design a new conceptual framework in the strategic management department of the National Iranian Gas Export Company (NIGEC), as well as the main components of the conceptual framework. It first goes through the logic behind the techniques applied to design this conceptual framework, and then each component is explained as to why it works as part of an integrated conceptual framework. This new framework is part of a change regime in the organisation along with the whole oil industry in Iran aimed at contributing to directing the organisations confronted with rapidly altering environments. The insights of this study shed light on the basics of designing an adjusted conceptual framework for managers and researchers, and all companies faced with constant internal and external challenges and other characteristics of modern organisations.
Keywords: 350; conceptual framework; strategic management; organisational change; oil industry; Iran